Case 3739: Proposed conservation of usage of the specific names of Tipula marci Linnaeus, 1758 (currently Bibio marci) and Tipula febrilis Linnaeus, 1758 (currently Dilophus febrilis) by designation of a neotype for each (Insecta, Diptera, Bibionidae) - Skartveit, John; Haenni, Jean-Paul (Bulletin of Zoological Nomenclature, 2020)
The purpose of this application, under Article 75.6 of the Code, is to set aside all previous fixations of name-bearing types for the species Tipula marci Linnaeus, 1758 and Tipula febrilis Linnaeus, 1758 (currently Bibio marci and Dilophus febrilis, the St. Mark’s fly and the fever fly, respectively) and to designate neotypes in their place. Illustrations in pre-Linnaean works cited by Linnaeus in connection with these names are unidentifiable, and extant Linnaean syntypes of these two nominal species belong to other species than those for which the names have been consistently used since the early 19th century.
Keywords: Nomenclature; taxonomy; Insecta; Diptera; BIBIONIDAE; Bibio; Dilophus; Tipula marci; Tipula febrilis; Europe; neotype; St. Mark’s fly; fever fly